Riskante Projekte? : Ökonomische Praktiken und Mobilität von Händlerinnen in der Kolonie New Netherland - Brugger, Eva (My University, 2016)
This paper discusses economic practices of women in the Dutch colony New Netherland. As letters, court records and engravings show, women of the 17th century were involved in the colonial transatlantic and global trade of goods — predominantly fur — in many ways. Thus the dichotomous narratives of men as global players and women as locally bound are no longer justified. Instead, we need new perspectives that focus on the gender specificity of economic activities in Early Modern Times. Suggesting to analyze the history of global enterprises in the 17th century as a history of projects this paper focuses on the risks of failure and their impact on the economic behavior of men and women alike.
Keywords: Frauen; Geschichte; Kolonialismus; Wirtschaft; 900 Geschichte; 17. Jahrhundert; Handel